(untitled) (Journal of Institute of Science and Technology, 2019)
Dust colour temperature, dust mass, visual extinction and Planck function with their distributions in the core region of two far infrared cavities (named FIC04+61 and FIC11-54) found within 3° of AGB stars namely AGB0409+6105 and AGB1105-5451 were studied. Dust colour temperature of the core region of the cavities was found to be (19.4 ± 0.93) K to (20.6 ± 0.65) K and (21.4 ± 0.51) K to (22.6 ± 0.23) K, respectively. The product of dust colour temperature and visual extinction was consistent in the order of 10-4. The contour maps showed that the low-temperature region has greater mass density and suggests that the distribution of dust mass is homogeneous and isotropic. The distribution of Planck function along with the extension (major diameter) and compression (minor diameter) found to be non-uniform distribution means dust particles were oscillating to get dynamical equilibrium. It further suggests that the dust particles in the cavities might not be in the thermal equilibrium possibly due to pressure-driven events of nearby AGB stars. A negative slope in the transition from 25 μm to 60 μm was our finding regarding far infrared spectral distribution in the cavities. It suggests that the number density of dust particles was less than expected in 60 μm regions.